The Use of Digital-Based English Learning Methods at Early Childhood Education Levels: A Structural Literature - Puspitasari, Tita; Narawaty, Dede (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This study aims to examine the structural literature review of digital-based English learning methods at the Early Childhood Education (ECE). The method used is a qualitative method. Data collection used in this study by searching for articles related to English learning at the Early Childhood Education using the Publish or Perish application. From the search results, 100 articles were found on learning various subjects based on digital-based education, with details of 19 articles on learning languages other than English and 81 articles in the field of English learning for all levels (ECE, PS, JHS, SHS, and University). The focus of this study is on 8 articles on digital-based English learning at the ECE level. This research method is a structural literature study by collecting information from relevant journal articles. The findings show that digital-based English learning at the ECE level has 8 digital-based learning methods, namely: fun early childhood learning strategies through the TPR (Total Physical Response Method), storytelling, pictures and songs; phonics method; Asset Based Communities Development (ABCD) method; bilingualism program with singing method and TPR (Total Physical Response) with the utilization of audiovisual media; picture message games; pictures and soft skills, and lapbook media. This study is a preliminary research for those who wants to follow up and deepen the similar topic.